2018
DOI: 10.1182/bloodadvances.2018017418
|View full text |Cite
|
Sign up to set email alerts
|

Significant gynecological bleeding in women with low von Willebrand factor levels

Abstract: Gynecological bleeding is frequently reported in women with von Willebrand disease (VWD). Low von Willebrand factor (VWF) may be associated with significant bleeding phenotype despite only mild plasma VWF reductions. The contribution of gynecological bleeding to this phenotype has yet to be described. The optimal clinical bleeding assessment tool (BAT) to evaluate bleeding remains unclear. Using a standardized approach to phenotypic assessment, we evaluated gynecological bleeding and directly compared the Cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
149
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 93 publications
(160 citation statements)
references
References 31 publications
10
149
0
1
Order By: Relevance
“…In line with our results, one study also mentioned the value of a Bleeding Assessment Tool, as the only woman diagnosed with a bleeding disorder was also the only patient who reported more than two additional bleeding symptoms. 23 Based on these and our data, maintaining higher plasma VWF levels could be considered during the peripartum period, in addition to early administration of TXA. This might indicate that, although there is a physiological increase in plasma VWF levels during pregnancy, 9,22 some women with low VWF apparently still are at risk for PPH.…”
Section: Discussionsupporting
confidence: 51%
“…In line with our results, one study also mentioned the value of a Bleeding Assessment Tool, as the only woman diagnosed with a bleeding disorder was also the only patient who reported more than two additional bleeding symptoms. 23 Based on these and our data, maintaining higher plasma VWF levels could be considered during the peripartum period, in addition to early administration of TXA. This might indicate that, although there is a physiological increase in plasma VWF levels during pregnancy, 9,22 some women with low VWF apparently still are at risk for PPH.…”
Section: Discussionsupporting
confidence: 51%
“…For example, in a recent single‐center retrospective study of 86 pregnancies in 55 women with VWD, all patients underwent third trimester monitoring, yet the incidence of primary PPH was 6.9%, similar to our findings in a population with much lower rates of screening . One cause of high rates of PPH despite third trimester monitoring may be current guidelines that recommend VWF replacement to > 50%, although recent studies suggest we are undertreating women with VWD with this approach and should rather be aiming closer to the levels of 150% to 200% that occur postpartum in the general population …”
Section: Resultssupporting
confidence: 84%
“…16 One cause of high rates of PPH despite third trimester monitoring may be current guidelines that recommend VWF replacement to > 50%, 5,18 although recent studies suggest we are undertreating women with VWD with this approach and should rather be aiming closer to the levels of 150% to 200% that occur postpartum in the general population. 11,[18][19][20] In conclusion, we found that third-trimester VWF monitoring was associated with a lower risk of PPH, but that testing was performed in only one-third of insured pregnant women with VWD in the United States despite expert recommendations. We also identified PPH events reported late (>2 weeks) in the postpartum period, and identified women presenting with HMB in the first 12 weeks after delivery.…”
Section: After Application Of Our Inclusion and Exclusion Criteria 2238mentioning
confidence: 77%
“…1 Women with VWD are at risk of a variety of bleeding complications during pregnancy owing to invasive prenatal procedures and the haemostatic challenge of delivery. 2 Retrospective studies found that women with VWD have also a higher rate of postpartum haemorrhage (PPH) and of transfusion at the time of delivery. 2,3 In the last decade, there has been increased research in women with inherited bleeding disorders including VWD.…”
Section: A Single-centre Study Of Management Of Pregnant Women With Vmentioning
confidence: 99%